ANALISIS VALUASI EKONOMI POTENSI PBB P2 YANG HILANG ATAS PENGENAAN TEGAKAN KEBUN KELAPA SAWIT MASYARAKAT - Sugaragiri, Seno Sakti; Aribowo, Irwan (Polytechnic of State Finance STAN, 2023)
Law number 12 of 1994 which forms the basis of PBB P5L stipulations and law number 1 of 2022 which forms the basis of PBB P5L stipulations have the same basis for imposition of land and buildings, but furthermore the land NJOP PBB P5L also takes into account plants as The stand is in the form of BIT, so that in an example case with the same tax object conditions it will produce different tax assessments. PBB P2 revenue has an effect on PAD, so taking into account the plants in the NJOP of PBB P2 land will provide significant revenue potential. This study aims to determine the impact of oil palm plantations if it is also taken into account in the NJOP of PBB P2. This research was conducted by requesting data from the Regional Government of Tebo Regency, then recalculating the PBB with the Tebo Regency Regional Regulation number 8 of 2020 which is adjusted to the BIT regulated in 186/PMK.03/2019. So that significant results were obtained for Rimbo Ulu District, the difference between the determination of lands NJOP PBB P2 taking into account plants and not was Rp. 10,073,520.00 and for Tebo Regency was Rp. 499,330,560.00.